Review: cosmetic applications of bee venom - El-Wahed, Aida A. Abd; Khalifa, Shaden A. M.; Elashal, Mohamed H.; Musharraf, Syed G.; Saeed, Aamer; Khatib, Alfi; Tahir, Haroon Elrasheid; Zou, Xiaobo; Al Naggar, Yahya; Mehmood, Arshad; Wang, Kai; El-Seedi, Hesham R. (MDPI, 2021)
Bee venom (BV) is a typical toxin secreted by stingers of honeybee workers. BV and BV therapy have long been attractive to different cultures, with extensive studies during recent decades. Nowadays, BV is applied to combat several skin diseases, such as atopic dermatitis, acne vulgaris, alopecia, vitiligo, and psoriasis. BV is used extensively in topical preparations as cosmetics and used as dressing for wound healing, as well as in facemasks. Nevertheless, the safety of BV as a therapeutic choice has always been a concern due to the immune system reaction in some people due to BV use. The documented unfavorable impact is explained by the fact that the skin reactions to BV might expand to excessive immunological responses, including anaphylaxis, that typically resolve over numerous days. This review aims to address bee venom therapeutic uses in skin cosmetics.